Pijat Punggung Terhadap Perubahan Skala Insomnia di UPT Panti Sosial Penyantunan Lanjut Usia Waipare - Maria Fransiska Ronalia (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Sleep disorders is one of the health problems often faced by the elderly. This condition needs serious attention. This study aims to explain the Effect of Back Massage Therapy Against Changing Insomnia Scale in The Elderly in UPT Panti Sosial Penyantunan Lansia Padu Wau Waipare. This type of research uses quasi experimental method or Quasi experiment. The population in this study who experienced insomnia 28 people in UPT Panti Sosial Penyantunan Lansia Padu Wau Waipare. In this study nonprobability sampling with total sampling technique. Data collected Observation using Wilcoxon test. The results showed that the scale of insomnia before given Back Massage Therapy (back massage) most categories of Insomnia Scale is as many as 23 people (82.1%). Insomnia scale after given Back Massage Therapy (back massage) at most categories of light Insomnia Scale as much as 19 people (67,9%). Statistical test results Wilcoxon Signed Ranks Test shows significant value 0.000 Value <0.05, Ha is accepted because 0.000 <0.05, there is effect of back massage therapy on insomnia scale changes in the elderly In UPT Panti Sosial Penyantunan Lansia Padu Wau Waipare. Researcher expect to improve quality of sleep of elderly who experience insomnia hence required therapy Back massage.